Prosocial Behavior at Work Through the Lens of Character Strengths - Freidlin, Pavel; Littman-Ovadia, Hadassah (Frontiers in Psychology, 2020)
Character strengths are positive traits that have been shown to efficiently and effectively promote a host of positive outcomes, outside and inside the workplace. Despite their theoretical moral basis, they have not been systematically and wholly explored as antecedents of, and correspondingly unused as, mechanisms to increase prosocial behaviour at work. Prosocial behaviour at the workplace is desirable, with research pointing to a host of organizational benefits. The utilization of character strengths toward prosocial behaviour at work seems like a missed opportunity, given that character strengths have been demonstrated as robust positive mechanisms and given that they are characterized by qualities that are accommodating of the complexity of prosocial behaviour: distinct, value-laden, manifest behaviourally, cognitively and emotionally, are plural and sensitive to individual differences and are capable of balancing positive and negative outcomes. The current article will encourage further understanding, examination and implementation of character strengths at the workplace, specifically for prosocial purposes, by exploring their conceptual fit and by reviewing initial empirical evidence.